Digital signal processing for accurate body temperature measurement - Koshekov, Abay; Orazbayeva, Bibigul; Savostin, Alexey (Bulletin of Electrical Engineering and Informatics, 2025)
The relevance of the subject matter is conditioned by the need to find the most effective and stable point for measuring body temperature using special measuring instruments. The main purpose of this scientific research is to develop a method for the most accurate implementation of these operations through the use of scientific and theoretical apparatus of digital signal processing. The study used methods of analysis and synthesis of information about the main provisions necessary in the process of finding an effective place for measuring the temperature parameter. The main points of body temperature measurement were established, including the key provisions of the digital temperature signal processing technique for measuring these parameters, which are required to assess the real state of a person. The presented mathematical formulas reflect the possibilities of calculating the average body temperature, as well as the skin temperature parameter, determined depending on the temperature indicators at individual points. Temperature curves for various types of diseases were presented. The practical significance of the results obtained lies in the possibility of their use in the activities of institutions of various profiles to find an effective method of measuring human body temperature to assess the physical condition.